2022
DOI: 10.21449/ijate.1132980
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen desteğinin ve sınıf içi öğretim uygulamalarının okuma başarısındaki rolü: PISA 2018 sonuçlarından Türkiye için çıkarımlar

Abstract: The study deals with the variation of Turkish students' reading comprehension performance according to perceived teacher support and reading activities in the classroom. This study, which is grounded on the data drawn from the PISA 2018 database, investigates the relationship between certain variables. In the analyses performed on the PISA IDE server, the PISA 2018 reading literacy general averages of Türkiye were associated with the identified variables, and the differences in the averages were examined. As a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…Although empirical evidence is not lacking, the extant literature has yielded inconsistent findings. While some studies have shown that teacher feedback is associated with reading performance (Gu & Lau, 2023;Meng et al, 2017), other studies have found either a negative or insignificant contribution (Bozkurt, 2022;Qian & Lau, 2022). Similarly, the link between teacher-directed instruction and reading literacy is positive in some studies (e.g., Karaman, 2022), but negative in the others (e.g., Hu & Wang, 2022;Ma et al, 2022;Qian & Lau, 2022).…”
Section: Instructional Practices and Reading Performance: A Review Of...mentioning
confidence: 96%
See 1 more Smart Citation
“…Although empirical evidence is not lacking, the extant literature has yielded inconsistent findings. While some studies have shown that teacher feedback is associated with reading performance (Gu & Lau, 2023;Meng et al, 2017), other studies have found either a negative or insignificant contribution (Bozkurt, 2022;Qian & Lau, 2022). Similarly, the link between teacher-directed instruction and reading literacy is positive in some studies (e.g., Karaman, 2022), but negative in the others (e.g., Hu & Wang, 2022;Ma et al, 2022;Qian & Lau, 2022).…”
Section: Instructional Practices and Reading Performance: A Review Of...mentioning
confidence: 96%
“…These include individual factors such as individual reading practices and motivation, as well as school factors such as teaching practices and classroom support for reading growth and engagement. Among these factors, high-quality instructional practice is of great importance (Bozkurt, 2022;Karaman, 2022;Qian & Lau, 2022). High-quality instructional practice builds foundational reading skills, and promotes reading motivation and engagement (Haw & King, 2022;Nurmi et al, 2013).…”
Section: Reading Literacy: Pisa 2018 Reading Performance Assessment F...mentioning
confidence: 99%
“…For example, in a quasi-experimental study with 456 students from 23 schools, it was found that the reading achievement of students in classes where adaptive instruction was implemented was higher than that of students in classes where traditional methods were preferred (Houtveen et al, 1999). Other studies on this subject also indicated that there were significant relationships between adaptive instruction methods and students' achievement in reading (Bozkurt, 2022;Karaman, 2020) and in other areas (Bazán-Ramírez, 2022;Forbes et al, 2020). Research also suggested that such an approach can produce beneficial outcomes in terms of students' affective and psychological attributes like motivation and academic self-concept (Erdoğdu, 2020;Lau & Ho, 2020).…”
Section: Adaptive Instruction and Reading Achievementmentioning
confidence: 99%